An examination of the application of a geographical information system to rural development planning in Shixini Location, Transkei - Whisken, Jarrell Braden (Rhodes University, Faculty of Science, Department of Geography, 1996)
Digital geographical information systems (GIS) are tools for handling spatial data. Initially developed in First World countries, the technology is fast being taken up as a tool for handling spatial information by many Third World countries. GIS has been used for any number of applications involving spatial data, one of its primary uses has been in various planning fields where the advantages offered to planners by the technology have been highlighted by a number of publications and studies. GIS has been actively used as an urban planning tool in South Africa since the mid-1980s, (Vosloo 1987) however its use as a tool for rural planning has not developed to the same extent. As early as 1986 reference was made to the possible advantages offered by GIS to rural planning in South Africa (Fincham 1986). Despite this early recognition, the use of GIS in the rural planning sphere remains negligible. This study examines the. possible reasons for this by attempting to answer the question, "is GIS appropriate to rural planning in South Africa?" A number of approaches to rural planning are practised in South Africa. This study examines the appropriateness of applying GIS to one of these approaches, rural community development planning. Components of the study included i) an examination of the issues affecting the use of GIS in the rural development field, achieved through the use of a literature and questionnaire survey and ii) a case study examining the feasibility of incorporating GIS as a tool to the Shixini Development Project, Transkei. The study does not examine the intricacies of rural development theory, but it does acknowledge the fact that the approach employed by an organisation to rural development will have important implications concerning the use of a GIS in a project. The approach adopted to a project affects amongst others the administrative structure, the planning process, the flow of spatial data and its use, and consequently the possible role of GIS. The Shixini Rural Development Project was classified as a community development project, and as a result the study concentrates on this approach to rural development. This may limit the study to a particular planning process, however most rural case studies will have certain aims and factors which are unique to its situation. In order to place the results of the Shixini case study in a wider context the results of the study are linked to the questionnaire and literature survey. From this basis the usefulness of GIS in the rural development sphere was examined. Available literature on GIS indicates that the majority of problems associated with GIS rarely reside with the technology itself but rather with its supporting mechanisms. The study identified and concentrated on these support mechanisms, both at the project level and what is referred to in the study as the operating environment in South Africa. The results of the study revealed that a number of problems exist with regard to the attitude with which GIS is regarded in development organisations. It was found that these attitudes are legitimately based on a number of problems associated with incorporating the technology into project based organisations. It was concluded that GIS was appropriate to rural community planning, but is presently limited to certain aspects of the planning process and possibly to certain applications.
Keywords: Rural development projects -- South Africa -- Transkei -- Shixini -- Planning; Shixini rural development project; Geographic information systems